Pengaruh Penerapan Sistem Proposional Terbuka Pada Kualifikasi Calon Legislatif - Sri Emut Ratnasara; Dwi Putri Cahyawati (JOURNAL of LEGAL RESEARCH, 2019)
AbstractPolitical parties in recruiting legislative candidates if only based on an open proportional system are not enough, especially if only in good faith to be able to become people's representatives. However, the most important thing needed is intellectual ability and integrity in understanding, both regarding legislation, as well as the main goal of achievement, which is to gain the benefit of all the people of Indonesia. Therefore, to produce politicians who are cultured or politicians who have dignity, self-esteem, and a clear way of thinking, a system that is in accordance with needs is needed. Due to the poor quality produced by legislators from various parties, political parties are not relevant in recruiting legislative candidates. By doing so, it is necessary to hold a fit and proper test in the selection of candidates for legislative members by external political parties that have standardization of graduation for candidates for legislative members. Besides the application of an open proportional system, it has a great influence on determining the quality of legislative members. With the implementation of an open proportional system, it will cause many popular legislative candidates to be elected without considering the capacity of the ability of legislative candidates who occupy positions, as well as allowing each candidate to compete to win public sympathy and will trigger a polemic over money politics.Keywords: Proportional System, Recruitment, Legislative Candidates